The Impact of Nursing Intervention on Pain Management among Children with Chronic Illnesses in the Pediatric Intensive Care Unit - Ali, Zainab H.; Kadheim, Zainab T. Abdul (Journal of Science in Medicine and Life, 2026)
Background: ain control represents a fundamental component of care for children with chronic conditions admitted to the pediatric intensive care unit (PICU). Insufficient management of pain may adversely affect both the physical and psychological well-being of pediatric patients. Therefore, this study was conducted to assess the effectiveness of nursing interventions in improving pain management among children with chronic illnesses in the PICU. A randomized controlled trial was employed in this study and carried out in the pediatric intensive care unit of a specialized hospital. The study involved a selected group of pediatric patients diagnosed with chronic illnesses, who were randomly assigned to either an intervention group or a control group. Data collection was performed using validated pain assessment tools and a nursing intervention observation checklist. Pain intensity was evaluated before and after the application of structured nursing interventions, which included routine pain assessment, pharmacological and non-pharmacological pain relief measures, and family participation in care. The findings demonstrated a statistically significant reduction in pain scores among children in the intervention group compared with those receiving standard care. These results indicate that structured nursing interventions were effective in enhancing pain control and improving patient comfort in the pediatric intensive care unit. The study concluded that nursing interventions play a significant and positive role in pain management for children with chronic illnesses in the PICU and recommends the adoption of standardized pain management protocols and ongoing nursing education to optimize pediatric care outcomes.Results: The comparison of FLACC pain scores before and after the intervention demonstrated a statistically significant reduction in pain levels following the implementation of nursing interventions. These findings confirm the effectiveness of nursing interventions in improving pain management among children with chronic illnesses in the pediatric intensive care uni..Conclusions: Based on the findings of the study, it can be concluded that nursing interventions have a vital role in enhancing pain management for children with chronic illnesses in the pediatric intensive care unit (PICU). The application of structured nursing interventions led to a significant decrease in pain intensity and a noticeable improvement in patient comfort. In addition, consistent pain assessment combined with both pharmacological and non-pharmacological approaches improved the quality of care and positively influenced patient outcomes. These results emphasize the essential contribution of nurses to effective pain management in the PICU. Recommendations: Ongoing education and training programs should be provided for nurses to strengthen their skills in pediatric pain assessment and management.